A PMU Placement Scheme Considering Realistic Costs and Modern Trends in Relaying - Pal, Anamitra; Vullikanti, Anil Kumar S.; Ravi, S. S. (IEEE transactions on power systems, 2017)
Synchrophasor deployment costs have evolved over time. The cost of upgrading a substation, which is much larger than the cost of an individual device, has emerged as the primary constituent of the total expenditure. Given these circumstances, the optimal phasor measurement unit placement formulation needs to consider not only the number of devices that must be placed at the substations, but also the number of substations that must be upgraded to support those devices. This paper presents an integer linear programming methodology for such a placement scheme while considering realistic costs and practical constraints. The IEEE 30 bus system is used to illustrate the proposed concept, while the IEEE 118, IEEE 300, and Polish 2383 bus systems are used to show the performance of the method under different test environments.